Diseño de un plan de marketing para el producto lisa college desarrollado por la microempresa browse Ecuador, ubicada en la ciudad de Quito. - Coello Duque, Giomar Evelyn (2013)
The present work aims to make a marketing plan for the product developed by Lisa College microenterprise Browse Ecuador Cia. Ltd. and it will be a guide for other micros companies wishing to conduct similar research. First, we review general information about the company under study in order to identify problems, research objectives and delimitation of the research area. With this knowledge provides the theoretical and conceptual framework underpinning this research. The start of the research is given to the analysis, diagnosis and strategic direction of the company. We have the SWOT as a critical result and defining of the mission, vision, policies, values and objectives.